Tolerancia religiosa en el republicanismo. El caso de Carlos E. Restrepo (2016)
ABSTRACT: This paper depicts, in broad terms, the ideology on religious tolerance that the political movement called Republicanism had in the early 20th century in Colombia. In particular, it focuses on the writings of former President Carlos Eugenio Restrepo. The text summarizes the difficulties of this leader born in Antioquia to segregate religious diatribes from the political exercise, its struggle for non-Catholic people to be accepted within the Republican Union, the support that gave the Protestant missionaries who arrived in Medellin and, in general, his openness to other religious ideas different to the ones from Roman Catholicism. The text states that the relationship between conservatism and the Catholic Church (conservatives politically allied with the clerics) does not have a single color, and that it is needed to expand the analysis scale to the point of personal relationships in order to perceive certain nuances.